PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA KELAS 4 SD - Galuh Setya Wardhani; Wasitohadi Wasitohadi (Universitas Negeri Medan, 2017)
Abstract : Application of Problem Based Learning Model with Picture Media to Increase Activity and Learning Outcomes of Graduate Students of Grade 4 Elementary School. The purpose of research to improve the activity and learning outcomes of science students fourth grade SD Keputon 01. Type of research is a classroom action research using the model of learning Problem Based Learning assisted media images. The research subjects of fourth grade students of SD Negeri Keputon 01. The results showed the average increase of the class before the action was 62.5, then in the first cycle the average rose to 72.9 and the increase in cycle II to 78.82. In addition, this success can be seen through the syntax of Problem Based Learning, which is 1) students' orientation on the problem, 2) organizing learners to learn, 3) guiding individual and group investigation, 4) developing and presenting the work, 5) analyzing the process of solving problem, which has been done 100%. Keywords : Activities and Learning Outcomes, Problem Based Learning, Students Abstrak : Penerapan Model Pembelajaran Problem Based Learning Berbantuan Media Gambar Untuk Meningkatkan Aktivitas Dan Hasil Belajar Ipa Siswa Kelas 4 SD. Tujuan penelitian untuk meningkatkan aktivitas dan hasil belajar IPA siswa kelas IV SD Keputon 01. Jenis penelitian adalah penelitian tindakan kelas yang menggunakan model pembelajaran Problem Based Learning berbantu media gambar. Subjek penelitian siswa kelas IV SD Negeri Keputon 01. Hasil penelitian menunjukkan peningkatan rata-rata kelas sebelum dilakukan tindakan adalah 62,5, kemudian pada siklus I rata-rata naik menjadi 72,9 dan peningkatan pada siklus II menjadi 78,82. Selain itu keberhasilan ini dapat dilihat melalui sintak Problem Based Learning, yaitu 1) orientasi peserta didik pada masalah, 2) mengorganisasikan peserta didik untuk belajar, 3) membimbing penyelidikan individu dan kelompok, 4) mengembangkan dan menyajikan hasil karya, 5) menganalisis proses pemecahan masalah, yangtelah terlaksana 100%. Kata Kunci : Aktivitas dan Hasil Belajar, Problem Based Learning, Siswa